Model-based displacement estimation of wind turbine blades using strain modal data. Issue 5 (September 2020) - Gundlach, J; Knebusch, J; Govers, Y; Haller, B
Abstract: For wind turbine rotor blades, the use of strain sensors is preferred over acceleration sensors for the purpose of permanent monitoring. Experimental modal analysis during operation is thus constrained to strain information, yielding strain modal data including strain mode shapes. For follow-up investigations such as aerodynamic load assessment or flutter monitoring it is however advantageous to have this information as displacement mode shapes or as displacements of the blade contour over time. This research applies a generic approach that converts strain mode shapes to displacement mode shapes utilizing an FE shell model as a basis for approximation. The accuracy of the approach is assessed by comparison with experimentally identified high-resolution displacement mode shapes which are acquired with accelerometers and serve as a reference. In the process the conversion procedure is illustrated with the help of strain data that has been obtained using a sensor instrumentation installed for certification testing of the blade. The requirements for successful usage of the employed conversion scheme and its suitability for rotor blade data are discussed.